ME AJUDA A RESOLVER SO ESSA AI EM CIMA
Anexos:
![](https://pt-static.z-dn.net/files/d47/93c4e59b219f5791cf80232983815cb1.jpg)
Soluções para a tarefa
Respondido por
1
.
Ola Cristina
(3^(n + 2) - 3^n)/(3^(n+1) - 3^(n -1)) =
(9*3^n - 3^n)(/3*3^n - 3^n/3) = (9 - 1)/(1 - 1/3) = 8//1/3) = 3 < resposta
Ola Cristina
(3^(n + 2) - 3^n)/(3^(n+1) - 3^(n -1)) =
(9*3^n - 3^n)(/3*3^n - 3^n/3) = (9 - 1)/(1 - 1/3) = 8//1/3) = 3 < resposta
cristina140:
esse riscos que vc bota nas letra e preciso colocar esses //
Perguntas interessantes
Ed. Física,
1 ano atrás
Química,
1 ano atrás
Geografia,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás